Towards Smart Tourism: An individual appreciation of Porlwi-By-Light festival: An Ordered Probit Approach - Boodnah, K.; Armoogum, V.; Jaunky, Vishal; Armoogum, S. (2016)
© 2016 IEEE.The festival of light is considered as one application of Smart Tourism to intelligently promote this sector. This paper examines how different socio-demographic and psychological aspects are complementary to attitude towards individual appreciation of the recent festival of light (Porlwi-By-Light). In order to obtain a precise description and understanding of individual perception, specific attempts have been carried out to control for personality traits and the anger scale of individual. The big five factor model of personality traits and individual anger scale are thereby considered. We apply a cross sectional data, captured from a drop-off survey with a sample size of 725 observations. Within an ordered probit and negative binomial framework, gender, age, residential location, educational level, family size, income, marital status, numbers of attendees at the festival, the extent to which they wish to go again to Porlwi-By-Light festival, whether it was a good season to organize the festival, the festival was appreciative, to extent to which the traffic jam affected the visitors, how the 5Es (education, entertainment, escapism, esthetics and economic value) contributed in the festival as well as personality traits and motivational factors, are found to be the conclusive factors affecting an individual appreciation at the festival. Our findings help us to draw consideration to the consequences of festival's experience and how personality-specific policies can be designed to influence public's perceptions.